A STUDY ON THE USE OF YOUTUBE IN LEARNING ENGLISH AMONG ENGLISH DEPARTMENT STUDENTS OF THE FACULTY OF LANGUAGES AND LITERATURE UNIVERSITAS NEGERI MAKASSAR - Syam, Sulhidayah; Samtidar, Samtidar; Munir, Munir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The objective of this research was to find out how YouTube is used as an English learning media among students in the second semester and fourth semesters of English Department Students of the Faculty of Languages and Literature, State University of Makassar.  This research used a purposive sampling technique with students in the second semester and students in the fourth semester. The study employed a qualitative method with a case study design. This research used questionnaires and semi-structured interviews as data collection methods. The results showed that students in this study used the YouTube application to learn English by watching content they liked, such as film and animation, music videos, educational, gaming, news, how-to, style, sports, food vloggers, talk shows, and religious content. The ways they learn to use YouTube are various, such as activating the subtitle or transcript feature, reading video titles or descriptions, reading comments, listening to music than looking for words they do not know, noting new vocabulary they hear from speakers, practicing pronunciation, etc. These things help them improve their English skills, specifically listening, enlarging their vocabulary, and increasing their pronunciation knowledge. In addition, YouTube provides fun English content with interesting YouTube features that make students more comfortable and enthusiastic about learning English, this also makes it easier for students to understand the material presented without getting bored. Students also expressed their challenges in using YouTube for learning English, such as inappropriate content, annoying advertisements, internet connection problem, and unavailability of the transcript feature on some videos. Based on the result, it can be concluded that most students of the English Education Study Program use the YouTube application to improve their English language skills and language components by watching English content they like by listening to the speaker, activating the subtitle or transcript feature, and read the title and comments on the video.